2015
DOI: 10.1117/12.2189818
|View full text |Cite
|
Sign up to set email alerts
|

The impact of radiation damage on photon counting with an EMCCD for the WFIRST-AFTA coronagraph

Abstract: WFIRST-AFTA is a 2.4m class NASA observatory designed to address a wide range of science objectives using two complementary scientific payloads. The Wide Field Instrument (WFI) offers Hubble quality imaging over a 0.28 square degree field of view, and will gather NIR statistical data on exoplanets through gravitational microlensing. The second instrument is a high contrast coronagraph that will carry out the direct imaging and spectroscopic analysis of exoplanets, providing a means to probe the structure and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The exact multiplication gain necessary to meet this requirement is dependant upon the baseline read-noise of the camera electronics, which itself depends upon the chosen pixel rate. The study performed by Harding et al (2015) 3 has shown that the baseline read noise remains below 90e…”
Section: Emccds For the Wfirst Cgimentioning
confidence: 99%
See 3 more Smart Citations
“…The exact multiplication gain necessary to meet this requirement is dependant upon the baseline read-noise of the camera electronics, which itself depends upon the chosen pixel rate. The study performed by Harding et al (2015) 3 has shown that the baseline read noise remains below 90e…”
Section: Emccds For the Wfirst Cgimentioning
confidence: 99%
“…10 Comparison to the results of room temperature irradiation described in Bush et al (2015) highlight a higher factor increase for an equivalent proton fluence when compared to the room temperature case. 23 Following a one week room temperature anneal period dark current was observed to return to what may be expected for a room temperature equivalent dose, measured as (1.14±0.10)×10…”
Section: Thermal Dark Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…Different irradiation conditions can be studied in intense detail and the impact and importance of cryogenic irradiations has been strongly demonstrated [21][22][23]. The technique is being used as a tool to understand the impact of radiation damage on CCDs for future mission studies, such as in the low-signal regime for WFIRST [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%